Manifestation of Violent Visions In Students - kizi, Sadullaeva (Indonesian Journal Publisher, 2025)
this article is aimed at studying the issue of the manifestation of violent perceptions in students. The purpose of the study is to analyze the Social, Psychological and cultural factors that influence the formation of violent perceptions in students. The study aims to identify students ' perceptions of violence and their interdependence using questionnaires, interviews, and psychological tests. Family education, stereotypes of peers and society play an important role in the formation of images of violence. The results of the study are aimed at proposing socio-educational measures to reduce violence in students.